O turismo nas mídias digitais : contratos enunciativos com o turista da atualidade - Machado, Andréia Ramos (2017)
The need for information in the current generation is dynamic and instantaneous. Tourism, as an important sector for the economy and society in general, also appropriates digital media to communicate with the new tourist profile. Therefore, this study aims to "Identify how tourism discourses establish contracts with the current tourist profile in digital media". In order to realize this objective, the study will take the Discourse Analysis as a theoreticalmethodological contribution and the bibliographical research for the theoretical reference on the subject. Initially, the concepts that compose the conditions of production of the texts included in the corpus of the research, which include the socio-historical, economic and cultural context that leave traces in the analyzed discourses, are approached. These concepts are distributed in the chapters: "Tourism: Globalization, Memory and Consumption" and "Communication in Tourism: Information, Virtualization and Digital Media". Afterwards, the Discourse Analysis method proposed by Patrick Charaudeau analyzes discursive marks that allow to recognize who the texts of the travel blogs makes speak, considering their instance of production, its enunciative context and the proposed contracts By the speech in question. We analyze blog posts on Viaje na Viagem, 360 Meridianos e Esse Mundo é Nosso. At the end, the relations between the established contracts and the profile of the current tourist are recognized, verifying that the speeches are constructed to provide information to the reader and use references that contemplate the profile of the tourist of the present time. Therefore, it increases the confidence of the tourist in this type of information, considering the authors as "consultants" of trip, paper that previously was only assigned to the professionals of tourist companies.